Catálogo de melhores práticas de gestão de pessoas em projetos de desenvolvimento de software - Burkard, Marcelo Falkowski (2024)
This study investigates people management practices in software development projects, aiming to compile a catalog of best practices for researchers and professionals in the field. The research highlights the critical importance of people in the execution of these projects, under both traditional and agile approaches. The work conducts a systematic literature review to identify common problems in people management in software projects and the effective practices to solve them. Utilizing four search engines: ACM, IEEE, Scielo and ScienceDirect, filtering primary studies in english language published between 2016 and 2023. Starting with 2495 non-duplicated primary studies, a detailed analysis of 63 studies was conducted, resulting in the identification of nine clusters of problems and sixteen distinct practices. These practices were validated by 31 experts, allowing them to be classified in terms of relevance. The findings reveal the predominance of interpersonal skills (soft skills) over technical skills (hard skills) and emphasize the importance of practices such as continuous feedback, open communication, and transparent management. This catalog serves as a resource for managers to assess and adapt practices to the specific reality of their projects.